Primary computing & digital technologies : knowledge, understanding and practice - Turvey, Keith; Potter, John; Burton, Jeremy; Allen, Jonathan (Lecturer in Information Technology); Sharp, Jane, 1966- (London: Learning Matters, SAGE, 2016)
"What do you need to know to teach computing in primary schools? How do you teach it? This book offers practical guidance on how to teach the computing curriculum in primary schools, coupled with the subject knowledge needed to teach it. This Seventh Edition is a guide to teaching the computing content of the new Primary National Curriculum. It includes many more case studies and practical examples to help you see what good practice in teaching computing looks like. It also explores the use of ICT in the primary classroom for teaching all curriculum subjects and for supporting learning in every day teaching. New chapters have been added on physical computing and coding and the importance of web literacy, bringing the text up-to-date. Computing is both a subject and a powerful teaching and learning tool throughout the school curriculum and beyond into many areas of children's learning lives. This book highlights the importance of supporting children to become discerning and creative users of digital technologies as opposed to passive consumers"-- Back cover.
Previous edition : Primary computing and ICT : knowledge, understanding and practice / Keith Turvey, John Potter, Jonathan Allen, Jane Sharp. 2014.
Includes bibliographical references and index.
Keywords: Computer-assisted instruction